The nursing process in postpartum consultations at Primary Health Care Units - Nayara Paes Garcia; Angelina Lettiere Viana; Fernanda Santos; Silvia Matumoto; Lauren Suemi Kawata; Karina Domingues de Freitas (SciELO, 2021)
ABSTRACT Objective: To identify the steps of the Nursing Process and integral care. Method: Document analysis study on medical and nursing consultations records during postpartum conducted in primary health units in inland São Paulo state. The analysis comprised the registered steps, the sequence of steps, and the approach of psychosocial questions. The data are presented by frequency, percentage, and the expressed content of care. Results: The analyzed records amounted to 341. Out of these, 100% presented History; 62.2%, Nursing Diagnosis; 5.3%, Planning; 99.1%, Implementation; and 50.1%, Evaluation. Regarding the sequence of steps, 47.5% of the medical records presented three steps. In the incorporation of the principle of integrality, a more frequent presence of the biological approach was observed. Conclusion: This study shows the change of practice of nurses, with efforts to register the Nursing Process, and that the integrality of care constitutes a challenge to surpass a model of care which is fragmented and decontextualized from the life conditions of people.